Wpływ Mickiewicza na rozwój polskiego pamiętnikarstwa (na przykładzie "Moich wspomnień" Aleksandra Jełowickiego) = Mickiewicz's impact on Polish memoirs (the example of Aleksander Jełowicki's "My memories") - Winek, Teresa (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
On behalf of the Lithuanian and Russian Lands Association Adam Mickiewicz issued a proclamation to Polish emigrants in France to write down their insurrectionary memories. The study discusses the texts arisen with the mentioned inspiration and published by Feliks Wrotnowski and, furthermore, documents the thesis that a part of "My memories" ["Moje wspomnienia"] by Aleksander Jełowicki is a slightly late response to Mickiewicz's appeal. The sections concerning the childhood and youth periods of a Parisian editor were clearly situated within "Sir Thaddeus" ["Pan Tadeusz"] context. Polish memoirs written in France in the thirties of XIX century became a pattern for the next generation involved in the preservation of Polish cultural heritage.
Keywords: Mickiewicz, Adam (1798-1855); Jełowicki, Aleksander (1804-1877); Powstanie Listopadowe - 1830-1831; pamiętnikarstwo polskie; Podole; the November Uprising; Polish memoirs; Podolia